The social worker of the Public System of Social Services: some selfies for the knowledge and the enunciation - Martín-Estalayo, Maribel; Muriel-Saiz, Mercedes; García-Giráldez, Teresa (Cuadernos de Relaciones Laborales, 2021)
The following article has as main objective to know and to enunciate aspects and times of the daily life of the Social Work and its professionals from twenty speeches of social workers of the Public System of Social Services of the geographic area of Madrid. As a selfie, a sequence of images about who they are and what they do, how they recognize themselves and how they want to be recognized are presented and analyzed, that is, questions about the professional configuration in a determinated institutional context. One of the ideas that runs through the text is that the current representations of Social Work, in the university and in the profession, reflect unequal and subordinate power relations, as historically have accompanied the professions performed by women. Neither the Social Services have ever become subjective rights, nor were the academic contents of the university transformed in depth after the Bologna Declaration. Between the aspirations of the duty to be and the realities of being, there is still a lack of a true exercise of self-knowledge and care that would allow us to gain a margin of freedom and undertake concrete political action that is coherent with the demands and needs of the people users.
Keywords: Social Work; Social Services; selfie; self-knowledge; subalternity